METODE TOPSIS DALAM PEMILIHAN LOKASI USAHA KONTER DAN SERVIS HANDPHONE DI KABUPATEN PRINGSEWU - ridhawati, eka - (Institut Teknologi dan Bisnis Diniyyah Lampung, 2025)
Currently, almost all individuals have smartphones. Some even have more than one smartphone. Because many consumers use smartphones, this is one of the interesting things in running a business by opening a cellphone repair service. In this digital era, smartphone counter and service businesses are increasingly important along with the rapid telecommunications industry. One of the successes of this business is determining a strategic business location. Choosing the right location can provide a competitive advantage in attracting customers and increasing revenue. Using the TOPSIS method in determining the best location to open a business based on criteria including; location, population density, community income, distance, environmental security. In determining the location, in the Pringsewu area using the TOPSIS method, the results of 3 areas that have good potential to open a business are the Gadingrejo area which has the highest preference value with a preference value of 1, higher than the Wates area with a value of 0 and the Sidoarjo area with a value of 0.5. So the most appropriate location is Gadingrejo because it best suits the criteria, namely a strategic location, community density around the location, community income, and close to public facilities and a level of security that supports